The mediating effect of character strengths on the relationship between clinical nurses' mental health literacy and work engagement - Yuan Zhao; Yuling Li; Linping Shang; Junhong An; Ruonan Zheng (BMC Nursing)
Abstract Background As the main force of clinical work, nurses' work engagement level will directly affect nursing quality. A high level of work engagement helps to improve nurses' work performance, quality of nursing, and job satisfaction. Mental health literacy education can effectively improve work engagement. This study focuses on evaluating the relationship between the character strengths, mental health literacy, and work engagement of clinical nurses to improve the mental health literacy of clinical nurses and further improve their work engagement level. Methods Through convenience sampling, a cross-sectional survey was conducted among 1,660 nurses in five Level III general hospitals in Shanxi, Hubei, and Shandong from November to December 2023. The survey used a personal demographic form, a three-dimensional character strengths questionnaire, a Chinese multiple mental health literacy scale, and a work engagement scale. This study used the SPSS PROCESS macro procedure and the bootstrap method to examine the role of character strengths in the mediation model of mental health literacy versus work engagement. Results The results showed that the character strengths, mental health literacy, and work engagement scores of 1660 clinical nurses were (55.66 ± 8.83), (12.01 ± 5.78) and (33.77 ± 6.67), respectively. The total effect of mental health literacy on work engagement was 0.470 (95% Cl: 0.429 ~ 0.509); the indirect effect was 0.313 (95% Cl: 0.273 ~ 0.355); the direct effect was 0.157 (95% Cl: 0.108 ~ 0.206); the mediation effect accounted for 66.68% of the total effect. Conclusion Studies have shown that mental health literacy and work engagement were positively correlated among nurses. Character strengths plays a mediating role between nurses' mental health literacy and work engagement. Therefore, nursing managers should pay attention to the mental health literacy of clinical nurses, strengthen the training of mental health knowledge, improve the mental health literacy of clinical nurses, and give full play to the character strengths to further improve the level of clinical work engagement.